The work of ISSMGE TC3 (geotechnics of pavements) and how it links to earthworks - Correia, A. Gomes (2012)
This volume provides an overview of developments in the design and construction of earthworks, in particular those associated with transport infrastructure. It includes case studies from across Europe, which summarize current design standards and national codes of practice. Geotechnical risk and performance are addressed with discussions on the long-term stability of cuttings and embankments, the causes of slope failure, and a variety of stabilization techniques including the introduction of drainage measures and electrokinetic geosynthetics. There is guidance on the specification for material testing, the practice of soil improvement, ground treatment, the reuse of materials and the use of engineered fill. Finally consideration is given to asset management and geotechnical data management, the effects of climate change and environmental impact so that performance-based design can be combined with carbon footprint and cost analysis.